New insights into the early stages of thermal oxidation of carbon/carbon composites using electrochemical methods. (November 2016) - Zhang, Cuijuan; Chen, Min; Paulson, Scott C.; Rateick, Richard G.; Birss, Viola I.
Abstract: Highly graphitic carbon/carbon (C/C) composites are susceptible to high temperature air oxidation, e.g., when they are employed in aircraft brakes, and yet little is understood about the initial stages of oxidation damage. The present work demonstrates, for the first time, that aqueous, room temperature, electrochemical methods can be used to understand the early stages of thermal oxidation of C/C composites after exposure to air at 300–700 °C. Electrochemistry is shown to be significantly more sensitive to detection of the initial changes in the C/C composite structure and the evolution of its surface area, as compared with traditional bench-top methods. Cyclic voltammetry experiments, carried out in sulfuric acid solutions, revealed that thermal corrosion initiates at temperatures as low as 400 °C, which is more than 200 °C lower than the temperature at which changes can be seen as both the carbon mass loss and pore volume increase in this work. Time-dependent potential scan rate data and AC impedance analysis have revealed new insights into the evolution of pores in these materials, demonstrating that the initial thermal corrosion process is dominated by the lengthening of pre-existing mesopores and micropores, rather than the formation of new pores.